Folate profiling in wild and transgenic rice - Abilgos Ramos, Riza (2010)
Quantitative profiling of mono- and polyglutamyl folates in rice was achieved using the microbiological assay (MA) and a newly developed liquid chromatography tandem mass spectrometry (LC-MS/MS) method. MA was used to screen 51 rice cultivars for their total folate content and LC-MS/MS was employed to measure naturally occurring mono- and polyglutamated forms of the vitamin in wild type, FPGS Os03g02030 knockout and transgenic lines with overexpressed FPGS genes and with folate binding protein from cowï¿½s milk (cFBP) and ratï¿½s liver (GNMT).